Competitors' reactions to big tech acquisitions: Evidence from mobile apps - Pauline Luise Affeldt; Reinhold Kesler (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Since 2010, Google, Apple, Facebook, Amazon, and Microsoft (GAFAM) have acquired more than 400 companies. Competition authorities did not scrutinize most of these transactions and blocked none. This raised concerns that GAFAM acquisitions target potential competitors yet fly under the radar of current merger control due to the features of the digital economy. We empirically study the competitive effects of big tech acquisitions on competitors in a relevant online market. We identify acquisitions by GAFAM involving apps from 2015 to 2019, matching these to a comprehensive database covering apps available in the Google Play Store. We find that competing apps tend to innovate less following an acquisition by GAFAM, while there seems to be no impact on prices and privacy-sensitive permissions of competing apps. Additionally, we find evidence that affected developers reallocate innovation efforts to unaffected apps and that affected markets experience less entry post-acquisition.
Keywords: K21; L41; L86; G34; 330; mergers and acquisitions; digital markets; GAFAM; apps; innovation; privacy; event study